Superoxide targeted "turn-on" fluorescence sensing enabled by a diselenide based quinoline probe and its in vitro anticancer activity in cancer cells. (15th March 2023) - Shelar, Divyesh S.; Malankar, Gauri S.; Singh, Pinky R.; Vaidya, Shashikant P.; Pinjari, Rahul V.; Manjare, Sudesh T.
Abstract : Synthesis of the first selenium containing quinoline probe, selective for superoxide detection via "turn-on" fluorescence response. The probe exhibited better anticancer activity than cisplatin. Abstract : The first organoselenium-based quinoline probe was successfully synthesized and characterized by common spectroscopic techniques. The probe was found to be selective and sensitive for superoxide detection over other reactive oxygen species (ROS), biothiols and metal ions, bearing "turn-on" fluorescence response with high photostability. The probe emitted strong yellowish-green fluorescence in the presence of superoxide with a 64 fold increase in fluorescence intensity. The detection limit of the probe was found to be 1.57 μM. The theoretical calculations strongly support the ICT mechanism for turn-on response. In addition, an in vitro cytotoxicity study revealed strong anticancer activity of the probe compared to the standard drug cisplatin in lung carcinoma (A549) and breast cancer (MCF-7) cells. The significantly high IC50 value (65.21 μM) indicated the better biocompatibility of the probe for normal cells (MDCK) and that it will be a compelling medication for lung carcinoma cells (IC50 = 2.14 μM) and breast cancer cells (IC50 = 1.81 μM).